Management of pediatric post-infectious neurological syndromes - Elena Bozzola; Giulia Spina; Massimiliano Valeriani; Laura Papetti; Fabiana Ursitti; Rino Agostiniani; Cristina Mascolo; Margherita Ruggiero; Chiara Di Camillo; Anna Quondamcarlo; Luigi Matera; Davide Vecchio; et al. (BMC, 2021)
Abstract Background Post-Infectious Neurological Syndromes (PINS) are heterogeneous neurological disorders with post or para-infectious onset. PINS diagnosis is complex, mainly related to the absence of any recognized guidelines and a univocal definition. Aim of the study To elaborate a diagnostic guide for PINS. Materials and methods We retrospectively analysed patients younger than 14 years old admitted to Bambino Gesù Children's Hospital in Rome for PINS from December 2005 to March 2018. Scientific literature using PubMed as research platform was analysed: the key words "Post-Infectious Neurological Syndromes" were used. Results A polysymptomatic presentation occurred in a percentage of 88% of the children. Motor signs and visual disturbances the most observed symptoms/signs were the most detached, followed by fever, speech disturbances, sleepiness, headache and bradipsychism. Blood investigations are compatible with inflammation, as a prodromal illnesses was documented in most cases. Normal cerebral spinal fluid (CSF) characteristics has been found in the majority of the study population. Magnetic resonance imaging (MRI) was positive for demyelinating lesions. Antibiotics, acyclovir and steroids have been given as treatment. Discussion We suggest diagnostic criteria for diagnosis of PINS, considering the following parameters: neurological symptoms, timing of disease onset, blood and CSF laboratory tests, MRI imaging. Conclusions We propose criteria to guide clinician to diagnose PINS as definitive, probable or possible. Further studies are required to validate diagnostic criteria.